PENGELOLAAN EKOSISTEM MANGROVE BERBASIS MITIGASI (Kasus Pulau-Pulau Kecil Taman Nasional Bunaken) - N.W. Schaduw, Joshian; Yulianda, Fredinan; G. Bengen, Dietriech; Setyobudiandi, Isdradjad (AgriSains, 2012)
Small islands is an area that is susceptible to various factors. One of the factors influencing the ecological factors. These ecological factors include climate change, sea level rise, natural disasters, abrasion, sedimentation, erosion and pollution. To minimize vulnerability the effectiveness of these coastal ecosystems is urgently needed. This research analyze vulnerability of small island, mangrove ecosystem effectiveness and management strategy of mangrove ecosystem based mitigation. This research use both primary and secondary data primer data was gathered by sampling, field observation, and questioner analysis Vulnerability index was analyzed using multi dimensional scaling method whereas vulnerability mapping was analyzed by analysis of geographic information system using the software Archive project 3.3. Stakeholders analysis was used for patterns and strategic management, through a technique SMART (Simple multi attribute rating technique) using the software Criterium decision plus. The results from this research are Bunaken Island have the highest vulnerability level, followed by the island of Manado Tua, Nain and the lowest Mantehage island. The main factors of vulnerability in small island Bunaken National Park Â is the area of mangrove ecosystems. Increased area of mangrove ecosystems will increase the effectiveness of mangrove ecosystems as a buffer zone as well as increase the capacity of these ecosystems on the social, economic, and governance dimension. Management scheme which can accommodate a variety of problems faced by the mangrove ecosystem of small islands is collaborative management by the government as the leading sector, with the highest priority on the management of the ecological dimension. Key words : Management, Mangrove ecosystem, mitigation, small island.